WHOLE-BODY VIBRATION EXERCISE IMPROVES FUNCTIONAL PARAMETERS IN PATIENTS WITH OSTEOGENESIS IMPERFECTA: A SYSTEMATIC REVIEW WITH A SUITABLE APPROACH - Sá-Caputo, Danubia C.; Dionello, Carla da F.; Frederico, Éric Heleno F. F.; Paineiras- Domingos, Laisa L.; Sousa-Gonçalves, Cintia Renata; Morel, Danielle S.; Moreira-Marconi, Eloá; Unger, Marianne; Bernardo-Filho, Mario (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Patients with osteogenesis imperfecta (OI) have abnormal bone modelling and resorption. The bone tissue adaptation and responsivity to dynamic and mechanical loading may be of therapeutic use under controlled circumstances. Improvements due to the wholebody vibration (WBV) exercises have been reported in strength, motion, gait, balance, posture and bone density in several osteopenic individuals, as in post-menopausal women or children with disabling conditions, as patients with OI. The aim of this investigation was to systematically analyse the current available literature to determine the effect of WBV exercises on functional parameters of OI patients. Materials and methods: Three reviewers independently accessed bibliographical databases. Searches were performed in the PubMed, Scopus, Science Direct and PEDro databases using keywords related to possible interventions (including WBV) used in the management of patients with osteogenesis imperfecta. Results: Three eligible studies were identified by searches in the analysed databases. Conclusion: It was concluded that WBV exercises could be an important option in the management of OI patients improving the mobility and functional parameters. However, further studies are necessary for establishing suitable protocols for these patients.